SOSIALISASI EKONOMI SYARIAH DI GAMPONG ATEUK LAMPHANG, SIMPANG TIGA, KABUPATEN ACEH BESAR - Ijal Fahmi; Zakaria Zakaria; Nasir Nasir; Irma Farnita; Ilyas Ilyas; Taufiq Iqbal; Ismail Ismail (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of socialization in the form of service is carried out so that partners can; 1) Understanding Islamic economics, 2) Creating an Islamic Economic Community (MES), 3) Being able to answer the challenges of advancing learning technology, and 4) Evaluating the Islamic economic system in partner villages. The implementation of this Community Service activity is carried out using lecture, tutorial, and discussion methods. The usefulness of this community service activity is evaluated through a questionnaire by testing the usefulness of the simulation device which is calculated from the perspective of the community/participant which is translated into three quality dimensions, namely 3 dimensions, namely: (1) Motivation; (2) responsiveness, and (3) usability index. The results of the evaluation concluded that the Tool Benefit Index assessed by SME managers calculated with the utility index resulted in a range of IKP values ​​of 86 which was in the range of b + 4c IKP < a. The existence of the IKP at this interval means that the SME managers state that the Islamic Economic Socialization activity is very useful to be implemented in Gampong Ateuk Lamphang, Simpang Tiga, Aceh Besar District..